Sistemas produtivos, disponibilidade de biomassa e atributos energéticos de caroço de açaí e resíduos de serrarias familiares, em várzea estuarina do Rio Amazonas - (:unkn) unknown (Universidade Federal do Amapá)
There is a concern of the society in establishing other mechanisms of obtaining of sustainable energy, like the one coming from forest biomass. The quantification, qualification and availability of forest residues may enable its use to promote energy for low-income communities in the Amazon estuary. The main objective was to evaluate the production systems, perform the energy characterization and verify the availability of açaí stone and residues from family microstrieria, in the Ilha das Cinzas (GurupáPA). The system of production of açaí by the agroextrativistas (for sale and consumption) was tested with monitoring of 50 stylized calendars filled by families of the Ilha das Cinzas. Mapping of açaizais of the Ilha was carried out. Fruit yield and processing were analyzed for one year. The yield and the production of different types of residues were evaluated in familiar smallholdings of the floodplain. The amount of waste from sawmills was determined by means of monitoring with the families in the Ilha das Cinzas for a year, with the aid of questionnaires and follow up of the process. Each expedition was carried out to verify and validate the monitoring system and to collect samples. From each residue (serragem, para and costaneira) evaluated, samples were collected to determine the apparent specific mass and moisture content. The dry mass was determined in a forced ventilation oven at 105 °C. It was observed that a higher production of açaí fruits occurs from May to September, defined as the harvest period. It was observed that a higher production of açaí fruits occurs from May to September, defined as the harvest period. The monitoring technique was effective, identifying well the harvesting period, and could be used to estimate the potential of the biomass of the stone and its variation throughout the year. It can be inferred that significant variation of productivity occurs due to the differentiation of management capacity and seasonality. The average pulp content was 21% and mean stone yield 79% and humidity 30%. The average specific dry mass (0,4 g.cm-3) and the variation of the enthalpy of the core enable it to be used for energy, whose optimization depends on equipment that maintains temperatures above 300ºC during the process. The most processed species in small micro-farms were pau-mulatto (n = 42), andiroba (n = 21) and fava (n = 2), totaling 27,3 m³ of processed wood from the 65 toras. The most sawed products in the four sawmills evaluated were tábuas (n = 691), pernamanca (n = 269) and ripa (n = 58). The products generated totaled a volume of 10 m³. The average yield of sawn wood was 37%. The percentage of residues varied for sawdust (54,18%), apara (16,45%) and costaneira (29,37%), independently of the species. The mean apparent mass specific of sawdust was 0,3 g.cm-3 for pau-mulato and 0,2 g.cm-3 for andiroba. The apparent specific mass at 0% was 0,7 g.cm-3 for apara and costaneira of pau-mulato and andiroba wood. The average moisture in the wet base was 36% and in the dry base 63%. Through the results obtained with the study the same can be used as a basis for future research related to the technology coming from the use of biomass
Keywords: Ilha das Cinzas (Itatupã, Gurupá, PA); Resíduo de madeira; Recursos energéticos; Biomassa; Biocombustíveis; Caroço de açaí; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA::GERACAO DA ENERGIA ELETRICA; CNPQ::CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS; GESTÃO E CONSERVAÇÃO DA BIODIVERSIDADE; ECOLOGIA